2019
DOI: 10.1002/jhbp.678
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in major secondary bile acid, hyodeoxycholic acid, was the main alteration in hepatic bile acid compositions in a hypertensive nonalcoholic fatty liver disease model

Abstract: Background Previous findings on hepatic bile acid compositions in nonalcoholic fatty liver disease (NAFLD) have been inconsistent and complicated. The aim of this study was to investigate the effects of steatosis on hepatic bile acid composition in a hypertensive NAFLD model without obesity and diabetes mellitus and compare hepatic bile acid composition between hypertensive rats with and without steatosis. Methods Two groups of hypertensive rats were studied: spontaneously hypertensive rats (SHR) fed with a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…Lake et al reported that the BA metabolomic profile of NASH livers exhibited increased levels of taurine, conjugated BA species, taurocholic acid, and taurodeoxycholic acid, but decreased levels of CA and glycodeoxycholic acid [19]. Another study reported that hydroxycholic acid was the main alteration in hepatic bile acid composition in a hypertensive NAFLD model [20]. Thus, there is no confirmed relationship between hepatic steatosis and bile acid levels.…”
Section: Discussionmentioning
confidence: 99%
“…Lake et al reported that the BA metabolomic profile of NASH livers exhibited increased levels of taurine, conjugated BA species, taurocholic acid, and taurodeoxycholic acid, but decreased levels of CA and glycodeoxycholic acid [19]. Another study reported that hydroxycholic acid was the main alteration in hepatic bile acid composition in a hypertensive NAFLD model [20]. Thus, there is no confirmed relationship between hepatic steatosis and bile acid levels.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found that fecal levels of HDCA were consistently higher in H-fed mice treated with yogurt. HDCA treatment reduced hepatic triglyceride levels in mice 54 and decreased blood glucose in LDL receptor KO mice 55 , while a decrease in HDCA was reported as the main BA alteration in a rat model of hypertensive NAFLD 56 . Collectively, the changes in the gut microbiota composition together with an increase in HDCA found in yogurt-treated obese mice likely contribute to the healthier metabolic phenotypes.…”
Section: Discussionmentioning
confidence: 93%
“…Studies have reported that both primary and secondary BAs synthesis were increased but hepatic bile signaling was suppressed 44 , 45 . Apart from that, study by Tang et al 46 and Kodama et al 47 reported that rats with hepatic steatosis showed upregulation of TCA and downregulation of hyodeoxycholic acid and taurohyodeoxycholic acid. Our findings suggested that the ETRF supplementation, as opposed to TRF, most likely to regulate and improve bile acids synthesis in fatty liver.…”
Section: Discussionmentioning
confidence: 97%